Association of Traditional Cardiovascular Risk Factors With Venous Thromboembolism: An Individual Participant Data Meta-Analysis of Prospective Studies. Issue 1 (3rd January 2017) - Mahmoodi, Bakhtawar K.; Cushman, Mary; Anne Næss, Inger; Allison, Matthew A.; Jan Bos, Willem; Brækkan, Sigrid K.; Cannegieter, Suzanne C.; Gansevoort, Ron T.; Gona, Philimon N.; Hammerstrøm, Jens; Hansen, John-Bjarne; Heckbert, Susan; et al.
Abstract : Background: Much controversy surrounds the association of traditional cardiovascular disease risk factors with venous thromboembolism (VTE). Methods: We performed an individual level random-effect meta-analysis including 9 prospective studies with measured baseline cardiovascular disease risk factors and validated VTE events. Definitions were harmonized across studies. Traditional cardiovascular disease risk factors were modeled categorically and continuously using restricted cubic splines. Estimates were obtained for overall VTE, provoked VTE (ie, VTE occurring in the presence of 1 or more established VTE risk factors), and unprovoked VTE, pulmonary embolism, and deep-vein thrombosis. Results: The studies included 244 865 participants with 4910 VTE events occurring during a mean follow-up of 4.7 to 19.7 years per study. Age, sex, and body mass index-adjusted hazard ratios for overall VTE were 0.98 (95% confidence interval [CI]: 0.89−1.07) for hypertension, 0.97 (95% CI: 0.88−1.08) for hyperlipidemia, 1.01 (95% CI: 0.89−1.15) for diabetes mellitus, and 1.19 (95% CI: 1.08−1.32) for current smoking. After full adjustment, these estimates were numerically similar. When modeled continuously, an inverse association was observed for systolic blood pressure (hazard ratio=0.79 [95% CI: 0.68−0.92] at systolic blood pressure 160 vs 110 mm Hg) but not for diastolic blood pressure or lipid measures with VTE. An important finding from VTE subtype analyses was that cigarette smoking was associated with provoked but not unprovoked VTE. Fully adjusted hazard ratios for the associations of current smoking with provoked and unprovoked VTE were 1.36 (95% CI: 1.22−1.52) and 1.08 (95% CI: 0.90−1.29), respectively. Conclusions: Except for the association between cigarette smoking and provoked VTE, which is potentially mediated through comorbid conditions such as cancer, the modifiable traditional cardiovascular disease risk factors are not associated with increased VTE risk. Higher systolic blood pressure showed an inverse association with VTE. Abstract : Supplemental Digital Content is available in the text.